Reform of Ghana’s main agricultural mechanization program to better meet the needs of smallholder farmers - CGIAR Research Program on Policies, Institutions, and Markets (2019)
IFPRI researchers, a CIMMYT engineer specialist and government officials from Ghana's Ministry of Food and Agriculture carried out an assessment of Ghana's Agricultural Mechanization Service Enterprise Center program. The recommendations from this assessment, taking into account good practices from other countries, were used by the government to improve the program’s inclusiveness and efficiency.